In situ study on enhanced heavy ion irradiation tolerance of porous Mg. (February 2018) - Li, Jin; Chen, Y.; Wang, H.; Zhang, X.
Abstract: Mg is known to be highly vulnerable to irradiation damage. Here we show, via in situ Kr ion irradiation studies inside a transmission electron microscope, that both defect density and size have been reduced substantially in porous Mg compared to dense coarse-grained Mg counterpart. Both prism and basal dislocation loops form at low dose in coarse-grained Mg, but basal loops dominate at a higher dose level. Meanwhile, in irradiated porous Mg, basal loops prevail throughout the entire irradiation process. Mechanisms that lead to enhanced irradiation tolerance of porous Mg are discussed.